2020
DOI: 10.1177/2329490620904952
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Strategies in E-Complaint Refusals: Textbook Advice Versus Actual Situated Practice

Abstract: This article reports on the representation and operationalization of interpersonal attention in complaint management by comparing business textbooks, service recovery research, and situated practice. While textbooks commonly recommend the use of interpersonal strategies when writing complaint refusals, service recovery research points toward contextual differences in this regard. We use an authentic sample of complaint refusals from an intercultural business-to-business setting to show that the decontextualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
(125 reference statements)
1
10
0
Order By: Relevance
“…To be clear, the contributions in this special issue are by far not the first ones to address this topic from the perspective of linguistics and discourse studies. A considerable number of studies have already been carried out focusing on discourse and language use in online service contexts (e.g., Bou-Franch and Garcés-Conejos 2019;Cenni and Goethals 2017;Creelman 2015;Georgopoulou and Spilloti 2015;Page 2014;Page et al 2014;Vásquez 2011;Zhang and Vásquez 2014;Depraetere et al 2020;Ho 2017;Orthaber 2019;Lillqvist et al 2016), with some of them combining rigorous linguistic analysis with a subsequent experiment to test the effectiveness of specific linguistic strategies (De Clerck et al 2019;Decock, De Clerck and Van Herck 2020;Fuoli et al 2020;Van Herck, Decock, De Clerck and Hudders 2021). What makes this special issue unique is that it presents -to the best of our knowledge -the first collection of articles focusing on this topic in a discourse-oriented journal.…”
mentioning
confidence: 99%
“…To be clear, the contributions in this special issue are by far not the first ones to address this topic from the perspective of linguistics and discourse studies. A considerable number of studies have already been carried out focusing on discourse and language use in online service contexts (e.g., Bou-Franch and Garcés-Conejos 2019;Cenni and Goethals 2017;Creelman 2015;Georgopoulou and Spilloti 2015;Page 2014;Page et al 2014;Vásquez 2011;Zhang and Vásquez 2014;Depraetere et al 2020;Ho 2017;Orthaber 2019;Lillqvist et al 2016), with some of them combining rigorous linguistic analysis with a subsequent experiment to test the effectiveness of specific linguistic strategies (De Clerck et al 2019;Decock, De Clerck and Van Herck 2020;Fuoli et al 2020;Van Herck, Decock, De Clerck and Hudders 2021). What makes this special issue unique is that it presents -to the best of our knowledge -the first collection of articles focusing on this topic in a discourse-oriented journal.…”
mentioning
confidence: 99%
“…On the other hand, a number of authors explored the growing assumptions that relationship building was key but demonstrated that a lack of relational elements did not necessarily compromise the effectiveness of customer service (Decock et al, 2020), employee appraisals (Van De Mieroop & Vrolix, 2014), or conflict interactions (Bülow et al, 2019), suggesting that explicit linguistic content remains central to business communication practice.…”
Section: How To Decide: Performative Materials Discourses With Multip...mentioning
confidence: 99%
“…Not surprisingly, most (48.4%) pedagogical attention to communication practices dealt with the specific communication technology used. A total of 44 articles examined both traditional communication formats, such as text documents (Bremner, 2014; Decock et al, 2020; Diaz, 2013; Duncan & Hill, 2014; Koskela, 2018; Maier & Anderson, 2014; Nell et al, 2018) and meetings (Baraldi, 2013; Ewing et al, 2019; Nielsen, 2013; Scott et al, 2013; Tiitinen & Lempiälä, 2022), and formats deemed new, including electronic and social media (Bülow et al, 2019; Hastings & Payne, 2013; Jameson, 2014; Jansen & Janssen, 2013; Kiddie, 2014; Machili et al, 2019; Macnamara & Zerfass, 2012; Marlow et al, 2018; Moore, 2019; Rapanta & Cantoni, 2017; Stephens & Barrett, 2016; Turnage & Goodboy, 2016), internal communication platforms (Anders, 2016; Aten & Thomas, 2016; Cardon & Marshall, 2015; Cowan & Horan, 2021; Darics, 2014, 2020; Gode, 2019; Madsen, 2016, 2017; Pazos et al, 2013; Porter, 2017; Rollins & Lewis, 2012; Uysal, 2016), cell phones (Washington et al, 2014), and teleconferencing (Halbe, 2012). Several authors addressed the increasing importance of interpersonal communication across various settings (Bradley & Campbell, 2016; Hynes, 2012; Jian & Dalisay, 2018; Mazzei et al, 2012; Van De Mieroop & Vrolix, 2014).…”
Section: An Analysis Of the Rhetorical Evolution In The Business Comm...mentioning
confidence: 99%
“…Empathy may be even more salient in face-to-face or mediated interactions. Research drew attention to the importance of empathy in customer interactions such as call-center phone calls (C. M. Clark et al, 2013), in rhetorically and emotionally complex situations such as e-complaint refusals (Decock et al, 2020), apologies (Bisel & Messersmith, 2012), and "bad news" conversations (G. L. Bradley & Campbell, 2014), in fostering a healthy workplace atmosphere (Mayfield & Mayfield, 2015;Yue et al, 2020), and in cross-cultural and intercultural encounters (Swartz et al, 2019).…”
mentioning
confidence: 99%